Remodeling of ER Membrane Contact Sites During Cell Division - Fang Yu; Khaled Machaca (Contact)
Membrane contact sites (MCS) provide specialized conduits for inter-organelle communications to maintain cellular homeostasis. Most organelles are interconnected, which supports their coordination and function. M-phase (mitosis or meiosis) is associated with dramatic cellular remodeling to support cell division, including the equal distribution of organelles to the two daughter cells. However, the fate of MCS in M-phase is poorly understood. Here we review recent advances arguing for differential remodeling of endoplasmic reticulum (ER) MCS with the plasma membrane (PM, ERPMCS) and the mitochondria (MERCS) during cell division.